IMPROVING REPRODUCTIVE HEALTH KNOWLEDGE THROUGH THE RESSIK PROGRAM (HEALTHY REPRODUCTION FOR STUDENTS WITHOUT ILLNESSES) AT PUBLIC SENIOR HIGH SCHOOL 2 MALANG - Astari, Asti Melani; Yuliatun, Laily; Choiriyah, Muladefi; Merdikawati, Ayut; Fevriasanty, Fransiska Imavike; Ruliatna, Etty Fitria (Caring: Jurnal Pengabdian Masyarakat, 2023)
AbstractReproductive health information for adolescent students is still considered taboo and has not yet been included in the school curriculum. A good understanding of adolescent reproductive health is crucial because adolescents are expected to have responsible attitudes and behaviors regarding the reproductive process. The high-risk sexual behaviors among adolescents are due to a lack of accurate knowledge about reproductive health and sexually transmitted diseases. This activity aims to enhance the knowledge of high school adolescents regarding reproductive health. The activity was held in November 2021 at Public Senior High School 2 Malang, involving male and female students. The activity was conducted through health education, discussions, and demonstrations about reproductive health. The chosen media for delivery were audiovisual materials (PowerPoint presentations and videos). Evaluation was carried out using pre-test and post-test questionnaires related to knowledge. The complete questionnaires underwent data analysis. The data analysis results from the participants, with a total of 218 respondents who thoroughly answered the provided questions, showed that the majority of participants were female (71%), aged 16 years (49.1%), from 10th grade (54.6%), enrolled in the science stream (66.6%), and had previously received information about reproductive health (77.1%). Furthermore, a significant difference in reproductive health knowledge scores was found among male students (p-value 0.000), while for female students, the difference was not significant (p-value 0.892). In conclusion, audiovisual educational media effectively enhances reproductive health knowledge.